Emission of Protons and Charged Pions in p + Cu and p + Pb Collisions at 3, 8, and 15 GeV/c - J. H. Kang; Y. C. Qian; B. C. Li; S. W. Wu (Advances in High Energy Physics)
We present an analysis of proton and charged pion transverse momentum spectra of p+Cu and p+Pb reactions at 3, 8, and 15 GeV/c in the framework of a multisource thermal model. The spectra are compared closely with the experimental data of HARP-CDP at all angular intervals. The result shows that the widths of the particle distributions in both p+Cu and p+Pb collisions decrease with increasing the angle for the same incident momentum.